Faktor-Faktor Yang Memengaruhi Purchase Intention Pada Layanan Community-Centric Digital Subscription - Rakha Athallah Syahputra; Diena Noviarini; Sabo Hermawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The subscription economy has expanded rapidly, yet it is increasingly challenged by subscription fatigue, which has encouraged the emergence of community-centric digital subscription models that shift value propositions from mere access to participation and value co-creation. This study aims to examine the determinants of purchase intention in such services by testing the effects of perceived enjoyment, perceived usefulness, and perceived risk on purchase intention, as well as the mediating role of perceived value. A quantitative approach was employed through an online survey of 210 Generation Z respondents in DKI Jakarta who were aware of community-centric digital subscription services, and the data were analyzed using SEM-PLS. The results indicate that perceived enjoyment and perceived usefulness have positive and significant effects on both perceived value and purchase intention, whereas perceived risk shows no significant effect on either perceived value or purchase intention. Furthermore, perceived value positively and significantly influences purchase intention and serves as the strongest determinant in the model; it also significantly mediates the relationships between perceived enjoyment and purchase intention and between perceived usefulness and purchase intention, but does not mediate the effect of perceived risk. These findings suggest that subscription intention in community-based services is primarily driven by enjoyable user experiences, perceived functional benefits, and overall value evaluations rather than by perceived risk considerations.